PENGARUH LOKUS KENDALI, KOMITMEN ORGANISASI DAN KINERJA TERHADAP PENERIMAAN DISFUNGSIONAL AUDIT - Kusuma, Gumulya Sonny Marcel; Handayani, Mella (Balance : Jurnal Akuntansi dan Bisnis, 2024)
This research aims to determine the influence of the variables locus of control, organizational commitment, and performance on the acceptance of dysfunctional audits. Researchers used convenience sampling to determine respondents for the sample. The sample collected was 41 government auditors who worked at the BPKP Office of South Sumatra Province. The analysis in this research includes respondent characteristics, descriptive statistics and SEM-PLS analysis. The test results show that there is a significant influence between locus of control on organizational commitment, organizational commitment on performance, and organizational commitment on the acceptance of dysfunctional audits. The research results also show that there is no significant influence between locus of control on acceptance of dysfunctional audits, locus of control on performance, and performance on acceptance of dysfunctional audits.